Археологічна карта поховальних пам’яток давньоруського Подолу Києва - Івакін, В.Г. (My University, 2012)
V. Ivakin. Archaeological Map of the Burial Monuments of Ancient Podil Kiev The article is devoted to the Àncient Russ cemetaries discovered in Kiev Podol in 1972–2008 years. At the time of the Viking Age cemetary of Podolian people was a Necropol I on the territory of future “the city of Yaroslav”. After the official Christianization in 988 most burials found at the Kiev city cemeteries that operate in the parafial and princes churches, and on the territories of monasteries. Podil Districts burials of XI—XIII centuries considered in the context of the planning structure of the mass of urban development. Today, archaeological research discovered eleven ancient cemeteries and a few individual burials. The peculiarities of topographic location in the Kiev region marked chronological groups. Anthropological analysis of the bone material allowed cemeteries to determine the social status of the population buried in them. On the basis of the studied material is composed archaeological map, which marked the ancient Russian city cemeteries and individual graves IX—XIII centuries.
Keywords: Ancient Rus; the city cemetery; burial complexes; anthropology; ritual